Front Cover. (17th April 2020) - Jimbo, Koji; Konuma, Takaaki; Mizukami, Motoko; Nagai, Etsuko; Oiwa‐Monna, Maki; Isobe, Masamichi; Kato, Seiko; Takahashi, Satoshi; Tojo, Arinobu
Abstract : The front cover image is based on the Letter to Editor* Telomere length in CD4 + and CD8 + T cells among long‐term survivors of adults after single cord blood transplantation by Takaaki Konuma** et al., https://doi.org/10.1111/ejh.13385 .***